PERAN STRES AKADEMIK DAN DETERMINASI DIRI TERHADAP KESEJAHTERAAN SUBJEKTIF PADA MAHASISWA PROGRAM MAGISTER DI KOTA BANDUNG - Syarifah Aini, - (2021)
ABSTRAK Penelitian ini bertujuan untuk mengetahui peran stres akademik terhadap kesejahteraan subjektif dan peran determinasi diri terhadap kesejahteraan subjektif pada mahasiswa program magister. Penelitian ini menggunakan pendekatan kuantitatif dengan model analisis regresi linear sederhana. Populasi dari penelitian ini adalah mahasiswa magister aktif dengan domisili kampus Kota Bandung, dengan jumlah sampel 135 mahasiswa. Scale of Positive and Negative Experience (SPANE) dan Satisfaction with Life Scale (SWLS) digunakan untuk mengukur kesejahteraan subjektif. Perceived Stress Scale (PSS-10) yang telah dimodifikasi agar sesuai dengan keadaan akademik digunakan untuk mengukur stres akademik. Basic psychological need satisfaction (BPNS) digunakan untuk mengukur determinasi diri. Hasil penelitian menunjukkan bahwa terdapat pengaruh stres akademik terhadap kesejahteraan subjektif dimana ketika stres akademik meningkat maka kesejahteraan subjektif mahasiswa menurun. Adapun terdapat pengaruh determinasi diri terhadap kesejahteraan subjektif dimana ketika determinasi meningkat maka kesejahteraan subjektifpun meningkat. ABSTRACT This study aims to determine the role of academic stress on subjective well-being and the role of self-determination on subjective well-being in master's program students. This study uses a quantitative approach with a simple linear regression analysis model. The population of this research is active master's students with campus domicile in Bandung City, with a sample of 135 students. The Scale of Positive and Negative Experience (SPANE) and Satisfaction with Life Scale (SWLS) was used to measure subjective well-being. The Perceived Stress Scale (PSS-10) which has been modified to suit academic conditions is used to measure academic stress. Basic psychological need satisfaction (BPNS) is used to measure self-determination. The results showed that there was an influence of academic stress on subjective well-being, when academic stress increased, the subjective well-being of students decreased. Meanwhile, there is an influence of self-determination on subjective well-being, when determination increasThis study aims to determine the role of academic stress on subjective well-being and the role of self-determination on subjective well-being in master's program students. This study uses a quantitative approach with a simple linear regression analysis model. The population of this research is active master's students with campus domicile in Bandung City, with a sample of 135 students. The Scale of Positive and Negative Experience (SPANE) and Satisfaction with Life Scale (SWLS) was used to measure subjective well-being. The Perceived Stress Scale (PSS-10) which has been modified to suit academic conditions is used to measure academic stress. Basic psychological need satisfaction (BPNS) is used to measure self-determination. The results showed that there was an influence of academic stress on subjective well-being, when academic stress increased, the subjective well-being of students decreased. Meanwhile, there is an influence of self-determination on subjective well-being, when determination increases, subjective well-being also increases.es, subjective well-being also increases.